Revealing Whole-Brain Causality Networks During Guided Visual Searching - Kiefer, Christian M.; Ito, Junji; Weidner, Ralph; Boers, Frank; Shah, N. Jon; Grün, Sonja; Dammers, Jürgen (Frontiers in Neuroscience, 2022)
In our daily lives, we use eye movements to actively sample visual information from our environment (‘active vision’). However, little is known about how the underlying mechanisms are affected by goal-directed behavior. In a study of 31 participants, magnetoencephalography was combined with eye-tracking technology to investigate how interregional interactions in the brain change when engaged in two distinct forms of active vision: freely viewing natural images or performing a guided visual search. Regions of interest with significant fixation-related evoked activity were identified with spatiotemporal cluster permutation testing. Using generalized partial directed coherence, we show that, in response to fixation onset, a bilateral cluster consisting of four regions (posterior insula, transverse temporal gyrus, superior temporal gyrus, and supramarginal gyrus) formed a highly-connected network during free viewing. A comparable network also emerged in the right hemisphere during the search task, with the right supramarginal gyrus acting as a central node for information exchange. The results suggest that all four regions are vital to visual processing and guiding attention. Furthermore, the right supramarginal gyrus was the only region where activity during fixations on the search target was significantly negatively correlated with search response times. Based on our findings, we hypothesize that, following a fixation, the right supramarginal gyrus supplies the right supplementary eye field with new information to update the priority map guiding the eye movements during the search task.